2021
DOI: 10.1186/s12864-021-08012-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of lncRNA-miRNA-mRNA ceRNA network in human aortic dissection

Abstract: Background Many studies on long chain non-coding RNAs (lncRNAs) are published in recent years. But the roles of lncRNAs in aortic dissection (AD) are still unclear and should be further examined. The present work focused on determining the molecular mechanisms underlying lncRNAs regulation in aortic dissection on the basis of the lncRNA-miRNA-mRNA competing endogenous RNA (ceRNA) network. Methods This study collected the lncRNAs (GSE52093), mRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 37 publications
(33 reference statements)
0
30
0
Order By: Relevance
“…It has been shown that genetic differences in ribosome occupancy can affect protein translation. 296 , 297 A thorough understanding of the consequences of genetic differences among individuals is an important step toward personalized medicine. For the treatment of persons with a viral infection, the aim is to better understand the heterogeneity among individuals and determine who is most likely to benefit from a specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genetic differences in ribosome occupancy can affect protein translation. 296 , 297 A thorough understanding of the consequences of genetic differences among individuals is an important step toward personalized medicine. For the treatment of persons with a viral infection, the aim is to better understand the heterogeneity among individuals and determine who is most likely to benefit from a specific treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The MEQ and PSQI were used to test the criterion validity. Confirmatory factor analysis was performed to determine construct validity using the Statistical Product and Service Software Automatically tool (SPSSAU) (retrieved from https://www.spssau.com ), which has also been used in previous studies [ 30 – 32 ]. All other statistical analyses were conducted using SPSS version 23.0 (IBM Corp., Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For the sake of elucidating the underlying transcriptional regulation mechanisms among genes, an lncRNA-miRNA-mRNA triple ceRNA network was constructed in IS, as in previously reported similar methods [ 17 19 ]. According to the four online databases (miRcode, miRDB, miRTarBase, and TargetScan), we integrated lncRNA-miRNA pairs and miRNA-mRNA pairs into the ceRNA network, which was visualized by Cytoscape (v3.8.0) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%